PENENTUAN PENGARUH ALIH FUNGSI LAHAN TERHADAP DEBIT BANJIR MENGGUNAKAN SISTEM INFORMASI GEOGRAFI (SIG) - Evi Kurniati (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2007)
The aim of this research was to model the flood discharge estimation caused by landuse change by using Geographical Information System (GIS). The research was conducted from May to August 2006 in Lesti Hulu watershed. The methods included three steps, comprising data (spatial and attribute) gathering in year 2000 and 2004, data processing, and validity test. The validity test was conducted using SIMODAS-ITB software. The biggest change was settlement areas that increase 9.21 %. The flood peaks n the same rainfall condition of 92.22 mm were 202.54 m3/sec in year 2000 and 208.66 m3/sec in year 2004. The model used in this research had a high accuracy. This statement was espoused by a simulated hydrograph, which was almost similar to observed hydrograph; with R2 values of 86.22% and 72.02% in years 2000 and 2004 respectively. The rational test showed that the ratio between direct v value of 2.402.775 m3 and modeled v value of 2.385.081,6 m3 was 0.993. This meant that the mathematical model for determining flood discharge using SIMODAS-ITB software was valid, and provided an accurate output.